Impact of asymmetric L4–L5 facet joint degeneration on lumbar spine biomechanics using a finite element approach - Jun Sung Park; Tae Sik Goh; Jung Sub Lee; Chiseung Lee (Scientific Reports)
Abstract This study investigated the effects of asymmetric facet joint degeneration on spinal behavior and adjacent structures using finite element analysis (FEA). Facet joints play a critical role in providing spinal stability and facilitating movement. Degenerative changes in these joints can lead to reduced spinal function and pain. Specifically, asymmetric degeneration occurs when one side deteriorates more rapidly due to alignment issues, subsequently impacting adjacent structures. In this study, facet joint degeneration grades (G00, G40, G42, and G44) were assigned to the L4–L5 segment to simulate spinal behavior during extension, left and right lateral bending, and left and right axial rotations. As degeneration progressed, the range of motion in the affected segment decreased, resulting in altered stress distribution across the intervertebral discs and posterior bone. The analysis showed that the posterior bending angle during extension decreased with increasing degeneration severity. Additionally, during lateral bending, the bending angle in the corresponding direction decreased, while the anterior bending angle increased. Maximum equivalent stress analysis of the intervertebral disc in the affected segment revealed a decreasing trend as degeneration worsened, a pattern also observed during extension, left lateral bending, and right axial rotation. In the G40 model, the maximum equivalent stress in the posterior bone of L4 and L5 exhibited a significant disparity between the left and right sides. These findings provide quantitative insights into the progression of spinal degeneration, enhancing our understanding of how asymmetric facet joint degeneration (FJD) affects spinal motion and adjacent structures.